Vulnerability assessment across the frontline of law enforcement and public health: a systematic review. (21st April 2022) - Enang, Iniobong; Murray, Jennifer; Dougall, Nadine; Aston, Elizabeth; Wooff, Andrew; Heyman, Inga; Grandison, Graeme
ABSTRACT: Assessing vulnerability is an international priority area across law enforcement and public health (LEPH). Most contacts with frontline law enforcement professions now relate to 'vulnerability'; frontline health responders are experiencing a similar increase in these calls. To the authors' best knowledge there are no published, peer-reviewed tools which specifically focus on assessing vulnerability, and which are specifically designed to be applicable across the LEPH frontline. This systematic review synthesised 33 eligible LEPH journal articles, retaining 18 articles after quality appraisal to identify assessment guidelines, tools, and approaches used relevant to either law enforcement and/or public health professions. The review identifies elements of effective practice for the assessment of vulnerability, aligned within four areas: prevention, diversion/triage, specific interventions, and training across LEPH. It also provides evidence that inter-professional/integrated working, shared training, and aligned systems are critical to effective vulnerability assessment. This systematic review reports, for the first time, effective practices in vulnerability assessment as reported in peer-reviewed papers and provides evidence to inform better multi-agency policing and health responses to people who may be vulnerable.